PEMBATALAN DESAIN INDUSTRI MENURUT PERATURAN PERUNDANG-UNDANGAN YANG BERLAKU DI INDONESIA TENTANG HAK DESAIN INDUSTRI (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NO.129PK/Pdt.Sus/2011) - MHD RASYID SIREGAR (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Saidin2. T. Keizerina Devi A3. Jelly Leviza Registration is absolute to gain an Industrial design Right. An industrial design which is not renewed can be revoked. An industrial design can be revoked by a request from the holder of the industrial design rights and by a civil lawsuit filed by another party. The case in the Ruling of Supreme Court of the Republic of Indonesia No.129PK/Pdt.Sus/2011 involves Silvyn AW (plaintiff) who is a merchant selling an industrial design registered in China with Registration Numbe ZL 2004 3 0018967 X dated May 20, 2004 which is before Honggo Siswanto (defendant) filed an application on February 27, 2007. Based on this case, the research formulates the problems such as how the mechanism of filing a lawsuit to revoke an industrial design is, how the legal provisions on the settlement of the dispute over an industrial design in case similarity is found in the core of the industrial design are, and how the legal consideration taken by the judges concerning the industrial design according to the ruling of the Supreme Court of the Republic of Indonesia No.129PK/Pdt.Sus/2011 is.Keywords: Revocation, Industrial Design, Registration Application